SIFAT KIMIA DAN SENSORI BROWNIES BERBAHAN BAKU TEPUNG MOCAF, JAGUNG DAN KEDELAI HITAM - Atia Fizriani; Nela Eska Putri; Nanda Triandita (FoodTech: Jurnal Teknologi Pangan, 2019)
Wheat flour is often used as the main ingredient for making brownies. Indonesia is one of the largest wheat flour importers. Diversification of food from local sources can reduce food imports such as wheat flour. The aim of this study was to determine the best formulation of mocaf flour, corn and black soybeans as raw material for the production of brownies based on chemical and sensory properties. There are 4 brownies formulations, Brownies A (100% mocaf flour), B (50% mocaf flour, 30% black soybeans flour, and 20% corn flour), C (50% mocaf flour, 25% black soybeans flour, and 25% corn flour), and D (50% mocaf flour, 20% black soybeans flour, and 30% corn flour). The result showed that brownies A had the highest carbohydrate content (60.74 ± 0.43%) and brownies B had the highest protein content (5.79 ± 0.03%) and crude fiber (2.71 ± 0,04%). The addition of black soybean flour which has high levels of protein and crude fiber affects to the protein and fiber content of the brownies. Brownies A was the most preffered in the attributes of texture, color, odor, and taste.